2016
DOI: 10.1016/j.nec.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic/Persistent Idiopathic Facial Pain

Abstract: Persistent or chronic idiopathic facial pain, often called atypical facial pain, is often used as a diagnosis of exclusion. It is chronic pain in a nonanatomically distributed area of the face and mouth that can be episodic or continuous and described as a nagging dull pain that at times is severe. It is associated with other chronic pain conditions, psychological abnormalities, and significant life events. Investigations are all normal and early treatment can prevent chronicity. A multidisciplinary biopsychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The best method of treating such patients is a combination of biopsychosocial treatments with anti depressant medications and behavioral therapy [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The best method of treating such patients is a combination of biopsychosocial treatments with anti depressant medications and behavioral therapy [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric and psychosocial disability have often been associated with PIFP (23), although one study on 14 PIFP patients found no significant comorbid psychiatric disorders compared to controls (22). Increased scores for anxiety and depression are common, especially in PIFP patients reporting higher pain intensity (24), indicating that a psychiatric screening should be performed (25). Systematic screening revealed that 41.3% of patients suffering from PIFP or burning mouth syndrome (BMS) had an axis I disorder (major depression was the most frequent) before the onset of orofacial pain.…”
Section: Symptomatologymentioning
confidence: 99%
“…There is no specific treatment for PIFP. A multidisciplinary biopsychosocial approach with the use of antidepressant and antiepileptic drugs and psychological counseling helps relieve pain [8, 9]. In our case, the patient was obliged to stop carbamazepine because of general fatigue after the first administration.…”
Section: Discussionmentioning
confidence: 98%